INOVASI PEMBELAJARAN BIOLOGI MELALUI PENGEMBANGAN MEDIA VIDEO PENUNTUN PRAKTIKUM UNTUK SISWA SMA/MA - Wilma Sari; Nurhayati B (Jurnal Biogenerasi, 2023)
One of the innovations in biology learning today is developing conventional biotechnology practicum video media. This media was developed to determine the level of validity and practicality of video media for practicum on conventional biotechnology material for class XII MIPA at SMA Negeri 15 Luwu. This research was conducted using a research and development approach as well as a 4D development model. The 4D stage consists of 4 stages, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate on a small scale. Data from the assessment results from expert validators shows that the product developed is in the valid category so that it is feasible to use. The results of the trial in schools to obtain data on the practicality of the media obtained a score of 91.7% (very practical) by the teacher and the score obtained from students 83.3% (practical). Based on the research data, it can be concluded that the video media for practicum on conventional biotechnology material for class XII SMA/MA that has been developed meets the valid criteria and is very practical